Preparation method of high-concentration heteroatom-doped mesoporous carbon nanotube material and application of high-concentration heteroatom-doped mesoporous carbon nanotube material in lithium-sulfur battery
By using high-concentration heteroatom-doped mesoporous carbon nanotube materials in the positive electrode of lithium sulfur batteries, the problem of insufficient capacity and cycle stability of lithium sulfur batteries is solved, the specific capacity and rate performance are improved, and the battery is extended Service life.
Patent Information
- Application Number
- CN202411326133.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-13
AI Technical Summary
The rapid attenuation of lithium-sulfur batteries and insufficient cycle stability limit their practical application.
The self-template method is combined with the sol-gel method, and the polyphosphazene nanotubes are coated with SiO2 to prepare high-concentration heteroatom-doped mesoporous carbon nanotube materials for lithium-sulfur battery positive electrode to improve conductivity and heteroatoms. Retention rate, inhibit the polysulfide shuttle effect.
It significantly improves the specific capacity, rate performance and cycle life of lithium sulfur batteries. Through mesoporous structure and carbon nanotube materials with high heteroatom content, the conductivity of the sulfur positive electrode and the affinity for electrolyte are improved, and the multiple fixes are effectively fixed. Sulfide extends the battery's recycling life.
Smart Images

Figure CN119118115A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of positive electrode materials for lithium-sulfur batteries, and specifically relates to a preparation method of a high-concentration heteroatom-doped mesoporous carbon nanotube material and application thereof in lithium-sulfur batteries. Background Art
[0002] In the pursuit of a zero-emission society, the transportation and power industries are in urgent need of rechargeable high-energy density batteries. Lithium-sulfur batteries have significant advantages as secondary energy storage batteries. First, the reserves of elemental sulfur are sufficient, with an abundance of 0.05% in the earth's crust, and they are widely available and low in cost. Second, lithium-sulfur batteries have extremely high energy density. Lithium-sulfur batteries, which are composed of high-capacity sulfur and metallic lithium, have a theoretical energy density of up to 2600 Wh kg. -1 , several times that of traditional lithium-ion batteries, and is the next generation of high-energy-density batteries. However, the shuttle effect of the intermediate product polysulfide causes the capacity of lithium-sulfur batteries to decay rapidly, which seriously hinders their practical application.
[0003] The researchers mainly inhibit sulfide shuttling and improve reaction kinetics by modifying the materials in the sulfur positive electrode and designing the electrode structure. For example, conductive materials are used to improve electrode conductivity and sulfur utilization; polar porous materials are used to adsorb and fix polysulfides.
[0004] CN202410424832.X discloses a method for preparing a flexible lithium-sulfur battery positive electrode material containing heterogeneous structural materials. First, a carbon source, a niobium salt and a pore-forming agent are dissolved in a solvent to obtain a spinning solution, and a first product is obtained by electrostatic spinning; secondly, the first product is dried, and then subjected to a pre-oxidation treatment and a pore-forming carbonization treatment, and the obtained second product is mixed with selenium powder under a reducing atmosphere, and a selenization treatment is performed to obtain a flexible electrode material; finally, the flexible electrode material is subjected to a sulfur-carrying treatment to obtain a lithium-sulfur battery positive electrode material containing a heterogeneous structural material. The heterogeneous structure in the positive electrode material prepared by the present invention is combined with porous carbon nanofibers to have an adsorption and catalytic effect on lithium polysulfide in lithium-sulfur batteries, which can effectively inhibit the "shuttle effect" of lithium polysulfide, promote the reaction kinetics of lithium polysulfide, and greatly improve the energy density and cycle stability of lithium-sulfur batteries.
[0005] CN202410594299.1 discloses a preparation method and application of a positive electrode material for a lithium-sulfur battery. The technical solution uses regularly arranged polystyrene balls or polymethyl methacrylate as a template to synthesize a three-dimensional ordered structure of a metal cobalt-nickel composite material, and then uses cobalt-nickel particles in the three-dimensional structure as a metal catalyst to in-situ grow carbon nanotubes in the three-dimensional ordered macroporous structure to obtain a positive electrode material with a multi-level structure. The rich pore structure and rich reactive active sites in the material not only provide a three-dimensional conductive interconnection network and a smooth ion migration channel, but also can buffer the electrode volume expansion effect and inhibit the dissolution and shuttling of polysulfides; secondly, cobalt-nickel has catalytic activity, which can effectively catalyze the conversion of lithium polysulfide and reduce the loss of active substances; finally, the CNT generated on the surface improves the conductivity of the material and plays a significant physical adsorption role on lithium polysulfide, thereby improving the performance of lithium-sulfur batteries.
[0006] Although these works have made good progress and achieved good results, there are still deficiencies in battery specific capacity and cycle stability, which affects the practical application of lithium-sulfur batteries. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a method for preparing a high-concentration heteroatom-doped mesoporous carbon nanotube material, which combines a self-template method with a sol-gel method to prepare a mesoporous carbon nanotube material with SiO 2 Coated polyphosphazene nanotubes, and then carbonized to prepare high-concentration heteroatom-doped mesoporous carbon nanotube materials. 2 The presence of promotes the formation of mesoporous structure and improves the retention rate of heteroatoms.
[0008] The present invention also provides a mesoporous carbon nanotube material doped with high concentration of heteroatoms prepared by the above method, wherein the material has a mesoporous structure and a high heteroatom content, and also has excellent electrical conductivity.
[0009] The present invention also provides a lithium-sulfur battery positive electrode prepared from the above-mentioned high-concentration heteroatom-doped mesoporous carbon nanotube material. The high content of heteroatoms such as N, P, S, etc. in the lithium-sulfur battery positive electrode can not only improve the polarity of the carbon material and the affinity to the electrolyte, promote the transmission of lithium ions in the electrode, but also fix polysulfides by chemical adsorption. The hollow structure of mesoporous carbon can physically confine polysulfides, thereby inhibiting the shuttle effect and significantly improving the specific capacity, rate performance and cycle life of the lithium-sulfur battery positive electrode.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a high-concentration heteroatom-doped mesoporous carbon nanotube material comprises the following steps: S1: Preparation of polyphosphazene nanotubes PZS: Dissolving hexachlorocyclotriphosphazene in a first organic solvent to obtain a solution A, dissolving 4,4-dihydroxydiphenyl sulfone and an acid-binding agent in a second organic solvent to obtain a solution B, adding the solution A dropwise to the solution B within a set dropwise addition time under stirring, and then reacting at room temperature under stirring for 10-15 hours. After the reaction is completed, centrifuging, washing, and drying to obtain polyphosphazene nanotubes PZS; S2: Preparation of PZS@SiO 2 : The polyphosphazene nanotubes PZS in step S1 are dispersed in deionized water to obtain solution C, and then anhydrous ethanol and ammonia water are added to solution C and ultrasonically treated, and then tetraethoxysilane is added thereto, and stirred at room temperature for 10-20 hours. After the reaction is completed, the solution is filtered and vacuum dried at room temperature to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : The powdered PZS@SiO 2 The sample was placed in a tube furnace, heated to the predetermined sample temperature under an inert atmosphere and kept warm, and then naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C materials: The NPS-C@SiO 2 The powder is added to an etching solution and stirred, then centrifuged, washed, and finally dried in vacuum at room temperature to obtain an NPS-C material.
[0011] Further, in step S1, the molar ratio of hexachlorocyclotriphosphazene: 4,4-dihydroxydiphenyl sulfone is 1:2-1:4; the molar ratio of hexachlorocyclotriphosphazene: acid binding agent is 1:7-1:10, and the set dropwise addition time is 12 minutes to 16 minutes.
[0012] Further, in step S1, the acid binding agent is triethylamine, the first organic solvent is one or more of toluene, acetone or tetrahydrofuran, and the volume is 50 ml-80 ml; the second organic solvent is the same as or different from the first solvent, and is one or more of toluene, acetone or tetrahydrofuran, and the volume is 50 ml-80 ml, and the volume ratio of the second solvent to the first solvent is 1:1-1:3.
[0013] Furthermore, in step S2, the volume of deionized water is 10 ml-20 ml; the volume ratio of tetraethoxysilane to ammonia water is 1:6-1:15; the volume ratio of ammonia water to deionized water is 1:3-1:6; the volume ratio of deionized water to anhydrous ethanol is 1:4-1:7; and the mass ratio of tetraethoxysilane to PZS is 1:1-1:4.
[0014] Furthermore, in step S2, the ultrasonic treatment time is 10 minutes to 60 minutes; and the vacuum drying time is 10 hours to 20 hours.
[0015] Furthermore, in step S2, a surfactant is also added. Specifically, the surfactant is dissolved in deionized water to obtain solution D, and then anhydrous ethanol, ammonia water and the PZS in step S1 are added to solution D to obtain solution E, and then tetraethoxysilane is added to the above solution E, and stirring is continued at room temperature for 10 h-20 h. After the reaction is completed, suction filtration is performed and vacuum drying is performed at room temperature to obtain powdered PZS@SiO 2 .
[0016] Furthermore, the surfactant is one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty acid polyoxyethylene ester and F127, and has a mass of 0.2 g-0.6 g.
[0017] Furthermore, in step S3, the predetermined temperature is 600°C-900°C, and the heating rate is 2°C / min-7°C / min.
[0018] Furthermore, in step S3, an inert gas is introduced as a protective gas, such as nitrogen, a rare gas, etc.
[0019] Furthermore, in step S4, the etching solution is HF or NaOH solution.
[0020] Furthermore, the concentration of the HF solution is 10 wt%-20 wt%, and the concentration of the NaOH solution is 2 M-3M.
[0021] The invention also discloses a high-concentration heteroatom-doped mesoporous carbon nanotube material prepared by the method.
[0022] Furthermore, the wall thickness of the high-concentration heteroatom-doped mesoporous carbon nanotube material is 30 nm-40 nm, it has a mesoporous structure, and the pore size distribution is 2 nm-10 nm.
[0023] The present invention also provides a lithium-sulfur battery positive electrode prepared from the above-mentioned high-concentration heteroatom-doped mesoporous carbon nanotube material.
[0024] Furthermore, the lithium-sulfur battery positive electrode is prepared by the following steps: S5-1: mixing the sublimated sulfur and the above-mentioned NPS-C material in a predetermined ratio, grinding and stirring to obtain a mixture; S5-2: The mixture is transferred into a sealed glass tube, kept warm in a tube furnace, and then subjected to a heat-melting treatment to obtain NPS-C@S; S5-3: Adding a conductive agent, a binder and a solvent to NPS-C@S and stirring evenly to obtain an electrode slurry; S5-4: The electrode slurry is vacuum dried and punched into sheets to obtain a positive electrode for a lithium-sulfur battery.
[0025] Furthermore, in step S5-1, the mass ratio of sublimated sulfur to NPS-C material is 7:1-7:5; the grinding time t1 is 0 h. <t1≤2 h。
[0026] Furthermore, in step S5-2, the temperature of the tube furnace is 155°C, and the insulation time t2 is 12 h≤t2≤24 h.
[0027] Furthermore, in step S5-4, vacuum drying is performed at 80°C-140°C for 10 h-14 h.
[0028] The invention also discloses the use of the lithium-sulfur battery positive electrode in a lithium-sulfur battery.
[0029] Furthermore, the preparation steps of the lithium-sulfur battery are as follows: first, the positive electrode of the lithium-sulfur battery is cut into a circular electrode piece with a diameter of 12 mm, and then the negative electrode material, electrolyte, separator, electrode shell and positive electrode material are used to assemble the battery.
[0030] Furthermore, the selected negative electrode material is lithium sheet; the separator is Celgard 2400; the electrolyte is 1M LiTFSI dissolved in DME:DOL=1:1 Vol% (containing 0.2 M LiNO 3 ) mixed solution.
[0031] The present invention has the following beneficial effects: (1) The present invention prepares polyphosphazene nanotubes based on a self-template method (a method using a reaction intermediate product as a template), and then uses a sol-gel method to prepare SiO 2 The coated polyphosphazene nanotubes PZS are finally carbonized at high temperature to prepare high-concentration heteroatom-doped mesoporous carbon nanotube materials. 2 It has good thermal and chemical stability. Coating on the surface of PZS can prevent polymer aggregation at high temperature, promote the formation of mesoporous structure, and improve the retention rate of heteroatoms. Therefore, the prepared high-concentration heteroatom-doped mesoporous carbon nanotube material has a mesoporous structure and a high heteroatom content, and also has excellent conductivity.
[0032] (2) The present invention enhances the interaction between polyphosphazene nanotubes and tetraethoxysilane by adding surfactants, thus promoting the formation of SiO 2Uniformly coated on the surface of polyphosphazene nanotubes.
[0033] (3) The high-concentration heteroatom-doped mesoporous carbon nanotube material of the present invention can improve the conductivity of the sulfur positive electrode and reduce the electrode resistance; the mesoporous hollow structure in the material can serve as a sulfur species encapsulation skeleton, which can provide abundant sulfur-carrying space, alleviate the volume expansion of the positive electrode during the battery cycle, and thus suppress the large volume fluctuation during the cycle. In addition, heteroatoms such as N, P, and S can improve the polarity of carbon materials, improve the affinity for electrolytes, promote lithium ion transmission, and can adsorb and fix polysulfides through physical confinement and chemical adsorption, and suppress the shuttle effect, opening up new ideas for the exploration and design of high-performance electrodes for lithium-sulfur batteries.
[0034] (4) Due to the mesoporous structure and high heteroatom content of the high-concentration heteroatom-doped mesoporous carbon nanotube material of the present invention, the specific capacity, rate performance and cycle life of the lithium-sulfur battery positive electrode based on the material of the present invention are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is the SEM image of the NPS-C material of Example 3; Figure 2 The nitrogen adsorption-desorption curve of the NPS-C material of Example 3; Figure 3 is the pore size distribution curve of the NPS-C material of Example 3; Figure 4 The nitrogen adsorption-desorption curve of the NPS-C material of Comparative Example 1; Figure 5 is the pore size distribution curve of the NPS-C material of Comparative Example 1; Figure 6 PZS@SiO without surfactant added 2 SEM images of Figure 7 PZS@SiO with surfactant added 2 SEM images of Figure 8 It is the XPS graph of the NPS-C material of Example 3; Fig. 9 The electrical performance test results of the NPS-C@S positive electrode of Example 1 are shown, wherein (a) is the cycle performance test result at 0.1 C, in which the upper curve is the relationship between the coulomb efficiency and the number of cycles, and the lower curve is the relationship between the specific capacity and the number of cycles; (b) is the charge and discharge curve at 0.1 C; Fig.10The electrical performance test results of the NPS-C@S positive electrode of Example 2 are shown, wherein (a) is the cycle performance test result at 0.1 C, in which the upper curve is the relationship between the coulomb efficiency and the number of cycles, and the lower curve is the relationship between the specific capacity and the number of cycles; (b) is the charge and discharge curve at 0.1 C; Fig.11 The electrical performance test results of the NPS-C@S positive electrode of Example 3 are shown, wherein (a) is the cycle performance test result at 0.1 C, in which the upper curve is the relationship between the coulomb efficiency and the number of cycles, and the lower curve is the relationship between the specific capacity and the number of cycles; (b) is the charge and discharge curve at 0.1 C; Fig.12 The electrical performance test results of the NPS-C@S positive electrode of Example 4 are shown, where (a) is the cycle performance test result at 0.1 C. In the figure, the upper curve is the relationship between the coulombic efficiency and the number of cycles, and the lower curve is the relationship between the specific capacity and the number of cycles; (b) is the charge and discharge curve at 0.1 C. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention.
[0037] As used in this invention, the meanings and sources of relevant abbreviations are listed below: SSA: Specific surface area PZS: polyphosphazene nanotubes (prepared by self-template method) HCCP: Hexachlorocyclotriphosphazene (Aladdin Reagent Co., Ltd., purity: 98%) BPS: 4,4-dihydroxydiphenyl sulfone (Aladdin Reagent Co., Ltd., purity: 99%) TEA: triethylamine (Aladdin Reagent Co., Ltd., purity: 99%) CTAB: hexadecyltrimethylammonium bromide (Aladdin Reagent Co., Ltd., purity: 99%) TEOS: Tetraethoxysilane (Aladdin Reagent Co., Ltd., purity: 99.99%) NH 3 ·H 2 O: Ammonia (Western Chemical Reagent Company, 25%-28%) NPS-C: N, P, S doped carbon nanotubes As used herein, the term "self-template method" refers to the process of using a material that forms a certain three-dimensional structure by itself as a template, depositing the atoms or ions of the material into the pores or on the surface of the template through physical, chemical or biological methods, and then removing the template to obtain the desired nanostructured material. The nanomaterials produced by this method have structural characteristics similar to the template pores.
[0038] As used herein, unless otherwise specified, numerical ranges include both the starting and ending values of the range. For example, when describing a temperature as "600° C.-900° C.," this means that both 600° C. and 900° C. are valid values for the temperature.
[0039] In the method for preparing the mesoporous carbon nanotube material doped with high concentration of heteroatoms according to the present invention, the mesopore diameter and specific surface area of the product depend on the influence of various factors, which will be described in detail below.
[0040] The method for preparing the high-concentration heteroatom-doped mesoporous carbon nanotube material of the present invention mainly comprises the following steps: S1: Preparation of polyphosphazene nanotubes PZS: Hexachlorocyclotriphosphazene is dissolved in a first organic solvent to obtain a solution A, 4,4-dihydroxydiphenyl sulfone and an acid-binding agent are dissolved in a second organic solvent to obtain a solution B, solution A is added dropwise to solution B within a set dropwise addition time under stirring, and then reacted at room temperature under stirring for 10-15 hours. After the reaction is completed, polyphosphazene nanotubes PZS are obtained through centrifugation, washing and drying.
[0041] In step S1, a self-template method is used to prepare polyphosphazene nanotubes using a reaction intermediate product having a certain stereostructure as a template, wherein the reactants hexachlorocyclotriphosphazene, 4,4-dihydroxydiphenyl sulfone and an acid binding agent are all known to those skilled in the art. In an embodiment of the present invention, triethylamine is used as an acid binding agent. The first solvent and the second solvent may be the same or different, and are each independently one or more of toluene, acetone or tetrahydrofuran.
[0042] S2: Preparation of PZS@SiO 2 : The polyphosphazene nanotubes PZS in step S1 are dispersed in deionized water to obtain solution C, and then anhydrous ethanol and ammonia water are added to solution C and ultrasonically treated, and then tetraethoxysilane is added thereto, and stirred at room temperature for 10-20 hours. After the reaction is completed, the solution is filtered and vacuum dried at room temperature to obtain powdered PZS@SiO 2 .
[0043] As known to those skilled in the art, if the polyphosphazene nanotubes are directly carbonized, since PZS will agglomerate at a high temperature above 700 degrees, resulting in the disappearance of its mesopores and only micropores, only porous carbon nanotube materials mainly composed of micropores can be obtained, and the heteroatom content is relatively low, which is not conducive to the loading of sulfur and the storage and fixation of polysulfides in subsequent applications. Therefore, in this step S2, since the polyphosphazene nanotubes themselves have a porous structure and some hydroxyl groups, other substances can be adsorbed on their surface, and SiO 2 Polyphosphazene nanotubes are coated. SiO 2 It has good chemical stability and thermal stability, will not react with the precursor PZS material at high temperature, and will not expand or shrink in volume. 2 The properties of SiO2 can prevent PZS from agglomerating at high temperatures, assist PZS carbonization, promote the formation of mesoporous structure, and inhibit its volume expansion or contraction. 2 The coating is beneficial to retain the heteroatoms (N, P, S atoms) of PZS and improve the retention rate of heteroatoms, which is beneficial to the adsorption of polysulfides to inhibit the shuttle effect of lithium-sulfur batteries. Figures 2 to 5 As shown, without SiO coating 2 In the case of carbonization, the pore size distribution of the material obtained is mainly micropores, and according to the present invention, when coated with SiO 2 After carbonization, the obtained material has a mesoporous structure mainly distributed in the range of 2 nm-10 nm. This is due to the SiO 2 and PZS are tightly bound at the interface, SiO 2 It acts as an external template, which can exert stress-stretching effect on the PZS component and maintain the morphology and mesoporous structure of PZS nanotubes during carbonization. In the final material, the mesoporous channels usually have good pore connectivity, which can provide abundant storage space for sulfur and polysulfides.
[0044] However, the inventors found that directly coating SiO on the PZS surface 2 When SiO 2 The coating is uneven, and there is some SiO on the PZS surface. 2 Microspheres aggregate, which affects the structure and properties of the final material. Therefore, in order to achieve a more uniform SiO 2Coating, the present invention uses a surfactant in the coating reaction process. The type of surfactant is not particularly limited, as long as it can stabilize the sol particles and prevent them from aggregating. For example, cationic surfactants, anionic surfactants and nonionic surfactants can be used. For example, the surfactant can include hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty acid polyoxyethylene esters and F127. In one embodiment of the present invention, hexadecyltrimethylammonium bromide is used as a surfactant.
[0045] Therefore, step S2 can be specifically as follows: dissolving the selected surfactant in deionized water to obtain solution D, then adding anhydrous ethanol, ammonia water and PZS to solution D to obtain solution E, then adding tetraethoxysilane to the above solution E, continuing to stir at room temperature for 10 h-20 h, and after the reaction is completed, filtering and vacuum drying at room temperature to obtain powdered PZS@SiO 2 .
[0046] By using surfactants, the interaction between polyphosphazene nanotubes and tetraethoxysilane was enhanced, making SiO 2 Can be better coated on the surface of polyphosphazene nanotubes. Figure 6 and Figure 7 As shown, without adding surfactant, the PZS@SiO 2 There are many microsphere aggregates on the surface, which leads to uneven surface. 2 There are almost no microsphere agglomerates on the surface, and the surface is more uniform, which is more conducive to subsequent carbonization.
[0047] S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2 The sample was placed in a tube furnace, heated to the predetermined sample temperature under an inert atmosphere and kept warm, and then naturally cooled to room temperature to obtain NPS-C@SiO 2 powder.
[0048] In step S3, PZS@SiO 2 Carbonization is performed. The carbonization temperature has a significant effect on the performance of the final material because the temperature is related to the conductivity and heteroatom content of the material. If the temperature is too low, the carbonization is incomplete; and generally, the higher the temperature, the higher the degree of graphitization of the carbon material and the higher the conductivity. However, too high a temperature will cause the heteroatom content to decrease, and N, P, and S atoms will be converted into gas and volatilized, thereby affecting the conductivity of the final material. Therefore, it is necessary to optimize the appropriate temperature. In the present invention, the carbonization temperature is 600°C-900°C.
[0049] S4: Preparation of NPS-C materials: NPS-C@SiO 2 The powder is added to an etching solution and stirred, then centrifuged, washed, and finally dried in vacuum at room temperature to obtain an NPS-C material.
[0050] The step S4 is to remove the surface-coated SiO 2 The etching step of the final NPS-C material is obtained. In the present invention, a HF solution with a concentration of 10 wt%-20 wt% or a NaOH solution with a concentration of 2M-3M is used as an etching solution. After a series of post-treatments, an NPS-C material with a mesoporous structure and a high heteroatom content is obtained.
[0051] The present invention also provides a lithium-sulfur battery positive electrode prepared from the above-mentioned high-concentration heteroatom-doped mesoporous carbon nanotube material. The lithium-sulfur battery positive electrode is prepared by the following steps: S5-1: mixing sublimated sulfur and the NPS-C material of the present invention in a predetermined ratio, grinding and stirring to obtain a mixture; S5-2: The mixture is transferred into a sealed glass tube, kept warm in a tube furnace, and then subjected to a heat-melting treatment to obtain NPS-C@S; S5-3: Adding a conductive agent, a binder and a solvent to NPS-C@S and stirring evenly to obtain an electrode slurry; S5-4: The electrode slurry is vacuum dried and punched into sheets to obtain a positive electrode for a lithium-sulfur battery.
[0052] The materials such as the conductive agent, binder and solvent used in the above preparation are all known to those skilled in the art and will not be described in detail here.
[0053] The following examples are only listed as examples of embodiments of the present invention and do not constitute any limitation to the present invention. It can be understood by those skilled in the art that modifications within the scope of the essence and concept of the present invention fall within the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products. Example
[0054] Embodiment 1: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of PZS@SiO 2 : 0.4 g CTAB was dissolved in 10 ml deionized water to prepare solution D, and then 0.2 g PZS, 70 ml anhydrous ethanol and 3 ml ammonia water were added to solution D and ultrasonically treated for 30 minutes to obtain solution E. Then 0.2 ml TEOS was added to the above solution E and stirred at room temperature for 16 h. After the reaction was completed, it was filtered three times and vacuum dried at room temperature for 10 h to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2 The crucible was placed in an alumina crucible, and then the crucible was placed in a tube furnace and high-purity nitrogen was introduced as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5 °C / min to 600 °C for carbonization and kept at this temperature for 3 h. After the reaction was completed, it was naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C: NPS-C@SiO 2 The powder was added to a 20 wt% HF solution and stirred for 3 h, after which the resulting solution was centrifuged and the centrifuged product was washed 3-4 times with deionized water, and finally dried under vacuum at room temperature for 24 h to obtain NPS-C material; S5: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0055] Embodiment 2: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of PZS@SiO 2 : 0.4 g CTAB was dissolved in 10 ml deionized water to prepare solution D, and then 0.2 g PZS, 70 ml anhydrous ethanol and 3 ml ammonia water were added to solution D and ultrasonically treated for 30 minutes to obtain solution E. Then 0.2 ml TEOS was added to the above solution E and stirred at room temperature for 16 h. After the reaction was completed, it was filtered three times and vacuum dried at room temperature for 10 h to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2 The crucible was placed in an alumina crucible, and then the crucible was placed in a tube furnace and high-purity nitrogen was introduced as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5 °C / min to 700 °C for carbonization and kept at this temperature for 3 h. After the reaction was completed, it was naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C: NPS-C@SiO 2 The powder was added to a 20 wt% HF solution and stirred for 3 h, after which the resulting solution was centrifuged and the centrifuged product was washed 3-4 times with deionized water, and finally dried under vacuum at room temperature for 2 h to obtain the NPS-C material; S5: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0056] Embodiment 3: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of PZS@SiO 2 : 0.4 g CTAB was dissolved in 10 ml deionized water to prepare solution D, and then 0.2 g PZS, 70 ml anhydrous ethanol and 3 ml ammonia water were added to solution D and ultrasonically treated for 30 minutes to obtain solution E. Then 0.2 ml TEOS was added to the above solution E and stirred at room temperature for 16 h. After the reaction was completed, it was filtered three times and vacuum dried at room temperature for 10 h to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2 The crucible was placed in an alumina crucible, and then the crucible was placed in a tube furnace and high-purity nitrogen was introduced as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5 °C / min to 800 °C for carbonization and kept at this temperature for 3 h. After the reaction was completed, it was naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C: NPS-C@SiO 2 The powder was added to a 20 wt% HF solution and stirred for 3 h, after which the resulting solution was centrifuged and the centrifuged product was washed 3-4 times with deionized water, and finally dried under vacuum at room temperature for 2 h to obtain the NPS-C material; S5: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0057] Embodiment 4: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of PZS@SiO 2 : 0.4 g CTAB was dissolved in 10 ml deionized water to prepare solution D, and then 0.2 g PZS, 70 ml anhydrous ethanol and 3 ml ammonia water were added to solution D and ultrasonically treated for 30 minutes to obtain solution E. Then 0.2 ml TEOS was added to the above solution E and stirred at room temperature for 16 h. After the reaction was completed, it was filtered three times and vacuum dried at room temperature for 10 h to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2 The crucible was placed in an alumina crucible, and then the crucible was placed in a tube furnace and high-purity nitrogen was introduced as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5 °C / min to 900 °C for carbonization and kept at this temperature for 3 hours. After the reaction was completed, it was naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C: NPS-C@SiO 2The powder was added to a 20 wt% HF solution and stirred for 3 h, after which the resulting solution was centrifuged and the centrifuged product was washed 3-4 times with deionized water, and finally dried under vacuum at room temperature for 2 h to obtain the NPS-C material; S5: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0058] Embodiment 5: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of PZS@SiO 2 : 0.6 g CTAB was dissolved in 20 ml deionized water to prepare solution D. Then 2.256 g PZS, 80 ml anhydrous ethanol and 3.6 ml ammonia water were added to solution D and ultrasonicated for 30 min to obtain solution E. Then 0.0.6 ml TEOS was added to the above solution E and stirred at room temperature for 16 h. After the reaction was completed, the solution was filtered three times and vacuum dried at room temperature for 10 h to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2 The crucible was placed in an alumina crucible, and then the crucible was placed in a tube furnace and high-purity nitrogen was introduced as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5 °C / min to 800 °C for carbonization and kept at this temperature for 3 h. After the reaction was completed, it was naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C: NPS-C@SiO 2 The powder was added to a 20 wt% HF solution and stirred for 3 h, after which the resulting solution was centrifuged and the centrifuged product was washed 3-4 times with deionized water, and finally dried under vacuum at room temperature for 2 h to obtain the NPS-C material; S5: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0059] Embodiment 6: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of PZS@SiO 2 : 0.2 g CTAB was dissolved in 15 ml deionized water to prepare solution D. Then 0.846 g PZS, 82.5 ml anhydrous ethanol and 3 ml ammonia water were added to solution D and ultrasonicated for 30 min to obtain solution E. Then 0.3 ml TEOS was added to the above solution E and stirred at room temperature for 16 h. After the reaction was completed, the solution was filtered three times and dried under vacuum at room temperature for 10 h to obtain powdered PZS@SiO 2 ; S3: Preparation of NPS-C@SiO 2 : Powdered PZS@SiO 2The crucible was placed in an alumina crucible, and then the crucible was placed in a tube furnace and high-purity nitrogen was introduced as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5 °C / min to 800 °C for carbonization and kept at this temperature for 3 h. After the reaction was completed, it was naturally cooled to room temperature to obtain NPS-C@SiO 2 powder; S4: Preparation of NPS-C: NPS-C@SiO 2 The powder was added to a 20 wt% HF solution and stirred for 3 h, after which the resulting solution was centrifuged and the centrifuged product was washed 3-4 times with deionized water, and finally dried under vacuum at room temperature for 2 h to obtain the NPS-C material; S5: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0060] Comparative Example 1: S1: Preparation of PZS: 0.05 g HCCP (0.144 mmol) was dissolved in 30 ml toluene to obtain solution A, 0.108 g BPS (0.432 mmol) and 0.33 g TEA (3.27 mmol) were dissolved in 15 ml acetone to obtain solution B, solution A was added dropwise to solution B under magnetic stirring within 15 minutes, and then magnetically stirred at room temperature for 10 hours, after the reaction was completed, the solution was centrifuged, and the centrifuged product was washed 3-4 times with acetone and deionized water, respectively, to obtain a white product, and finally the white product was dried in a vacuum oven overnight to obtain PZS; S2: Preparation of NPS-C: 0.5 g of PZS was put into an alumina crucible, and then the crucible was placed in a tube furnace and introduced with high-purity nitrogen as a protective gas. In an inert atmosphere, the temperature was raised at a rate of 5°C / min to 800°C for carbonization and kept at this temperature for 3 hours. After the reaction was completed, the crucible was naturally cooled to room temperature to obtain NPS-C powder. S3: Preparation of NPS-C@S cathode: Sublimated sulfur and NPS-C were mixed evenly in a mass ratio of 7:3, ground and stirred for 30 min to obtain a mixture, and then the mixture was transferred to a sealed glass tube, placed in a tube furnace at 155°C for 12 h, and subjected to hot melt treatment to obtain NPS-C@S; subsequently, carbon black, polyvinylidene fluoride and N-methyl-2-pyrrolidone were added to NPS-C@S, stirred evenly to obtain an electrode slurry, vacuum dried at 80°C for 12 h, and punched to obtain the NPS-C@S positive electrode.
[0061] Experimental example 1. Performance test of NPS-C material 1) Morphological characterization The NPS-C material of Example 3 was subjected to a scanning electron microscope test, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the NPS-C material prepared according to the method of the present invention is in the shape of nanotubes, and the tube diameter is uniformly distributed, and the tube wall thickness is about 30 nm-40 nm.
[0062] 2) Pore size distribution test The NPS-C materials in Example 3 and Comparative Example 1 were subjected to nitrogen adsorption and desorption tests to determine their pore structure and pore size distribution.
[0063] The specific test process is as follows: the specific surface area and micropore distribution tester of the equipment model is V-Sorb 4800TP of Guoyi Precision Measurement. The NSP-C materials in Example 3 and Comparative Example 1 are respectively subjected to vacuum degassing treatment at 200°C for 6 hours, cooled to room temperature under vacuum and weighed, and then the sample tube is transferred to the analysis station, and liquid nitrogen is added to the Dewar flask to provide a low-temperature environment for adsorption testing, wherein nitrogen is used as the adsorption medium and helium is used as the carrier gas, and a certain proportion of mixture is carried out and adjusted to a predetermined relative pressure level. The structure is presented in Figures 2 to 5 middle.
[0064] Figure 2 and Figure 4 The nitrogen adsorption and desorption curves of the NPS-C material of Example 3 and the NPS-C material of Comparative Example 1 are shown respectively. It can be seen from the curve results that the NPS-C material of Example 3 according to the present invention has a mesoporous structure, and the specific surface area of the material calculated by the BET method is 392 m 2 g -1 ; The NPS-C material of Comparative Example 1 is mainly composed of micropores.
[0065] Figure 3 and Figure 5The pore size distribution curves of the NPS-C material of Example 3 and the NPS-C material of Comparative Example 1 are shown respectively. It can be seen from the figure that the pore size of the NPS-C material of Example 3 according to the present invention is roughly distributed in the range of 2 nm-10 nm; while the pore size of the NPS-C material of Comparative Example 1 is substantially less than 1 nm.
[0066] based on Figures 2 to 5 The results show that compared with directly carbonizing PZS, the preparation method of the present invention, i.e., using SiO 2 Coating PZS and then high-temperature carbonization to prepare heteroatom-doped mesoporous carbon nanotube materials, the resulting material has a mesoporous structure. This is because SiO 2 It has good thermal and chemical stability, and coating on the PZS surface can prevent the polymer from agglomerating at high temperatures, thereby promoting the formation of mesoporous structure.
[0067] 3) Heteroatom content test The NPS-C material of Example 3 was subjected to XPS testing to determine its heteroatom content. The results are presented in Figure 8 middle.
[0068] As can be seen from the figure, the NPS-C material obtained by the preparation method of the present invention has a relatively high heteroatom retention rate, and the total heteroatom content reaches 41.7 wt%, of which N is 3.9 wt%, S is 4.6 wt%, and P is 13.7 wt%. High content of heteroatoms such as N, P, and S can improve the polarity of carbon materials, improve the affinity for electrolytes, promote lithium ion transmission, and can adsorb and fix polysulfides through physical confinement and chemical adsorption, inhibit the shuttle effect, and thus improve the performance of the battery.
[0069] 2. Cycling performance test of NPS-C@S cathode The NPS-C@S positive electrode in Examples 1 to 4 was subjected to a cycle performance test, and the specific process is as follows: The battery cycle performance and constant current charge and discharge curve tests were tested and analyzed on the Xinwei battery test system. When the NPS-C@S positive electrode was set as the working electrode, it was discharged first and then charged and cycled in sequence. The voltage range was 1.7-2.8V.
[0070] The results of the cycle performance tests of the NPS-C@S positive electrodes in Examples 1 to 4 are shown in Figures 9 to 12As can be seen from the figure, at a carbonization temperature of 600-900°C, the specific capacity, rate performance and cycle life of the NPS-C@S positive electrode based on the NPS-C material prepared by the present invention are relatively high. However, when the carbonization temperature is too high or too low, for example, below 600°C or above 900°C, the charge and discharge reversible capacity is relatively small, and the specific capacity decreases significantly with the increase in the number of cycles. This is because the carbonization temperature is related to the conductivity and heteroatom content of the material. Generally, the higher the temperature, the higher the degree of graphitization of the carbon material and the higher the conductivity; high temperature will cause the heteroatom content to decrease, and N, P, and S atoms will be converted into gas volatilization, so a suitable temperature is required. It can be seen from the figure that when the carbonization temperature is 800°C, the cycle performance of the obtained NPS-C@S positive electrode is the best, wherein the charge and discharge reversible capacity at 0.1C reaches 1215 mAh / g, and after 110 cycles, the capacity retention rate is 91.1%.
[0071] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the existing technology should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a mesoporous carbon nanotube material doped with high concentrations of heteroatoms, characterized in that: The following steps are involved: S1: Preparation of polyphosphazene nanotubes PZS: Dissolving hexachlorocyclotriphosphazene in a first organic solvent to obtain a solution A, dissolving 4,4-dihydroxydiphenyl sulfone and an acid-binding agent in a second organic solvent to obtain a solution B, adding the solution A dropwise to the solution B within a set dropwise addition time under stirring, and then reacting at room temperature under stirring for 10 h to 15 h. After the reaction is completed, centrifuging, washing, and drying to obtain polyphosphazene nanotubes PZS; S2: Preparation of PZS@SiO2: The PZS in step S1 is dispersed in deionized water to obtain a solution C, and then anhydrous ethanol and ammonia water are added to the solution C and ultrasonically treated, and then tetraethoxysilane is added thereto, and stirred at room temperature for 10 h-20 h. After the reaction is completed, the solution is filtered and vacuum dried at room temperature to obtain powdered PZS@SiO2; S3: Preparation of NPS-C@SiO2: The PZS@SiO2 in step S2 is placed in a tube furnace, heated to a predetermined sample temperature under an inert atmosphere and kept warm, and naturally cooled to room temperature to obtain NPS-C@SiO2 powder; S4: Preparation of NPS-C materials: The NPS-C@SiO2 powder in step S3 is added to the etching solution and stirred, then centrifuged, washed, and finally vacuum dried at room temperature to obtain the NPS-C material.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of hexachlorocyclotriphosphazene: 4,4-dihydroxydiphenyl sulfone is 1:2-1:4; the molar ratio of hexachlorocyclotriphosphazene: acid binding agent is 1:7-1:10, the set dropwise addition time is 12 minutes-16 minutes, the acid binding agent is triethylamine, the first organic solvent is one of toluene, acetone or tetrahydrofuran, and the volume is 50 ml-80 ml; the second organic solvent is one of toluene, acetone or tetrahydrofuran, and the volume is 50 ml-80 ml, and the volume ratio of the second solvent to the first solvent is 1:1-1:
3.
3. The preparation method according to claim 1, characterized in that: In step S2, the volume of the deionized water is 10 ml-20 ml; the volume ratio of tetraethoxysilane to ammonia water is 1:6-1:15; the volume ratio of ammonia water to deionized water is 1:3-1:6; the volume ratio of deionized water to anhydrous ethanol is 1:4-1:7; and the mass ratio of tetraethoxysilane to PZS is 1:1-1:
4.
4. The preparation method according to claim 3, characterized in that: In step S2, a surfactant is also added; step S2 includes dissolving the surfactant in deionized water to obtain a solution D, then adding anhydrous ethanol, ammonia water and the PZS in step S1 to the solution D to obtain a solution E, then adding tetraethoxysilane to the above solution E, and continuing to stir at room temperature for 10 h-20 h. After the reaction is completed, the solution is filtered and vacuum dried at room temperature to obtain powdered PZS@SiO2.
5. The preparation method according to claim 4, characterized in that: The surfactant is one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, fatty acid polyoxyethylene ester and F127, and has a mass of 0.2 g-0.6 g.
6. The preparation method according to claim 1, characterized in that: In step S3, an inert gas is introduced as a protective gas; the predetermined temperature is 600°C - 900°C, and the heating rate is 2°C / min - 7°C / min.
7. The preparation method according to claim 1, characterized in that: In step S4, the etching solution is HF with a concentration of 10 wt% - 20 wt% or a NaOH solution with a concentration of 2M - 3M.
8. A highly concentrated heteroatom-doped mesoporous carbon nanotube material prepared by the preparation method according to any one of claims 1 to 7.
9. A lithium-sulfur battery positive electrode, characterized in that: The lithium-sulfur battery cathode is prepared by the following steps: S5-1: Sublimed sulfur and the highly concentrated heteroatom-doped mesoporous carbon nanotube material according to claim 8 are mixed in a predetermined ratio and ground to obtain a mixture; S5-2: The mixture is transferred to a sealed glass tube, kept warm in a tube furnace, and then obtained as NPS-C@S through heat melting treatment; S5-3: A conductive agent, a binder, and a solvent are added to NPS-C@S, and after stirring evenly, an electrode paste is prepared; S5-4: The electrode paste is vacuum dried, and after punching, a lithium-sulfur battery cathode is obtained; Among them, in step S5-1, the mass ratio of sublimed sulfur to NPS-C material is 7:1 - 7:5; the grinding time t1 is 0 h < t1 ≤ 2h; in step S5-2, the temperature of the tube furnace is 155°C, and the heat preservation time t2 is 12 h ≤ t2 ≤ 24 h; in step S5-4, it is vacuum dried at 80°C - 140°C for 10 h - 14 h.
10. Use of the lithium-sulfur battery cathode according to claim 9 in a lithium-sulfur battery.
Citation Information
Patent Citations
Preparation method and application of heteroatom-doped porous carbon nano-tube
CN103896246A
Preparation method and application of core-shell-structured mesoporous carbon-coated multi-walled carbon nanotube composite material
CN107154485A
Thin-walled amorphous carbon nanotube, preparation method and application thereof
CN110510599A
Hybrid structure, sulfur-hybrid complex comprising the same, and method for producing hybrid structure and sulfur-hybrid complex
US20200262707A1
Cited By
Preparation method of mixed type soft and hard carbon material and application of mixed type soft and hard carbon material in sodium ion battery
CN119858913A
Positive electrode active layer composition, positive electrode plate and lithium iron manganese phosphate secondary battery
CN121306953A
